Pesticide sorption on soils treated with evergreen oak biomass at different humification stages (Communications in Soil Science and Plant Analysis, 1992)
Abstract The sorption of twelve pesticides (alachlor, atrazine, carbofuran, 2,4?D, 2,4?DB, methyl parathion, metoxuron, monuron, prometryne, propanil, silvex and spergon) was studied on two soil samples with a different carbonate content and treated with evergreen oak (Quercus ilex L. subsp. ballota) biomass at successive humification stages. The direct interaction between the above pesticides and lignocellulosic materials was also assayed independently. After the samples were suspended in 25 ppm pesticide solutions for 12 h, the concentrations in the supernatants were measured by derivatographic UV spectroscopy. The major fixations on the biomass of evergreen oak were found for spergon, prometryne and propanil. Except for atrazine, carbofuran, prometryne and silvex, composting the forest residue for 87 weeks significantly increased pesticide sorption. No correlations were found between the sorption values measured directly in the lignocellulosic materials and those in the soils amended with the latter, indicating the conspicuous influence of organo?mineral interactions in the soil. Calcium carbonate played an important role in pesticide sorption: the lowest pesticide retentions were observed for the samples of the soil with the highest pH, where the addition of organic matter led to the greatest enhancements. The fixation of silvex and carbofuran increased considerably when the organic matter was added to the soil with the lowest pH, whereas in the calcic soil samples the major fixation corresponded to chlorinated phenoxy acids. Possible mechanisms involved in pesticide sorption in the systems studied are discussed.
doi: 10.1080/00103629209368699